Current status and future directions of nanovaccine for cancer: a bibliometric analysis during 2004-2023 - Hou, Yuhui; Li, Yue; Zhang, Youao; Zhang, Juan; Wu, Dinglan (Frontiers in Immunology, 2024)
Background: Nanovaccine treatment is an exciting area of research in immunology and personalized medicine, holding great promise for enhancing immune responses and targeting specific diseases.Their small size allows efficient uptake by immune cells, leading to robust immune activation. They can incorporate immune-stimulating molecules to boost vaccine efficacy. Therefore, nanovaccine can be personalized to target tumor-specific antigens, activating the immune system against cancer cells. Currently, there have been ample evidence showing the effectiveness and potential of nanovaccine as a treatment for cancer. However, there was rare bibliometric analysis of nanovaccine for cancer. Here we performed a bibliometric and visual analysis of published studies related to nanovaccine treatment for cancer, providing the trend of future development of nanovaccine.We collected the literatures based on the Web of Science Core Collection SCI-Expanded database. The bibliometric analysis was performed via utilizing visualization analysis tools VOSviewer, Co-Occurrence (COOC), Citespace, Bibliometrix (R-Tool of R-Studio), and HitCite.Results: A total of 517 literatures were included in this study. China is the country with the most publications and the highest total local citation score (TLCS). The Chinese Academy of Sciences holds the largest research count in this field and the most prolific author is Deling Kong from Nankai University. The most prominent journal for publishing in this area is Biomaterials. The researches mainly focus on the therapeutic process of tumor nanovaccines, the particle composition and the application of nanovaccines, suggesting the potential hotspots and trends of nanovaccine. In this study, we summarized the characteristics and variation trends of publications involved in nanovaccine, and categorized the most influential countries, institutions, authors, journals, hotspots and trends regarding the nanovaccine for cancer. With the continuous development of nanomaterials and tumor immunotherapy, nanovaccine for cancer provides a research field of significant clinical value and potential application.